Generic group metacognitive therapy for depression in specialized mental health care: an open trial with 6- and 12-month follow-ups - Nordahl, Henrik; Pukstad, Erlend; Hjemdal, Odin; Veium, Lise T.; Strand, Eivind R. (Frontiers in Psychiatry, 2026)
IntroductionDepression is the most prevalent mental disorder and a common cause for seeking treatment in specialist mental health care settings. Along with having a broad negative impact on general functioning, depression is frequently comorbid with other mental disorders and can, in many presentations, be complex to treat, with substantial relapse rates following treatment. Metacognitive therapy (MCT) aims to modify common determinants of distress to improve mental regulation, making it a transdiagnostic treatment well suited for delivery in a group format.MethodsIn the present study, we evaluated the treatment effects associated with the generic group MCT in a Norwegian Specialist Mental Health Service for patients in need of treatment for depression. Diagnostic evaluation was conducted by independent assessors pre- and post-treatment, and patients self-reported on a range of measures pre-, post-treatment, and at six- and 12-month follow-ups.ResultsTwenty patients divided into four groups received group MCT delivered by two therapists over 10 sessions. The treatment was associated with an 80% recovery rate from depression and large effects across primary and secondary outcomes, including return to work. From post-treatment through the six- and twelve-month follow-ups, the improvements were largely maintained, but a few patients reported a clinically significant increase in depression symptoms. A health economic evaluation indicated that the treatment was cost effective.DiscussionThese findings suggest that generic group MCT is well-suited for specialist mental health care services aiming to treat depression cost-effectively.